2021
DOI: 10.1186/s12868-021-00660-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a new verbal working memory-balance program: a double-blind, randomized controlled trial study on Iranian children with dyslexia

Abstract: Background It is important to improve verbal Working Memory (WM) in reading disability, as it is a key factor in learning. There are commercial verbal WM training programs, which have some short-term effects only on the verbal WM capacity, not reading. However, because of some weaknesses in current verbal WM training programs, researchers suggested designing and developing newly structured programs that particularly target educational functions such as reading skills. In the current double-blin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(64 citation statements)
references
References 105 publications
6
58
0
Order By: Relevance
“…Participants were allocated into two groups by the block randomization method in a 1:1 ratio by a computer (Kim & Shin, 2014). Six blocks with a block size of 4 were considered in randomization to ensure a balance in sample size across groups (Ramezani et al, 2021). Participants in the control group received treatment by the VWM program as a traditional WM training.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were allocated into two groups by the block randomization method in a 1:1 ratio by a computer (Kim & Shin, 2014). Six blocks with a block size of 4 were considered in randomization to ensure a balance in sample size across groups (Ramezani et al, 2021). Participants in the control group received treatment by the VWM program as a traditional WM training.…”
Section: Methodsmentioning
confidence: 99%
“…Children with DD were eligible for the study if they had normal vision/hearing conditions, normal attention level as measured by CSI‐4, normal IQ score as measured by WISC‐IV, right‐handed, average socio‐economic status as reported by their families, and native‐Persian language (Ramezani et al, 2021). The subjects were formally diagnosed using a validated and reliable Persian battery of normative reading tests –NEMA (Moradi et al, 2016; Ramezani et al, 2021). Children who obtained a score of 25% or less for word reading efficiency and non‐word reading efficiency subtests of the NEMA in the preliminary screening entered the study (Moradi et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that developmental dyslexia in alphabetic languages was associated with sensorimotor deficits, balance, motor skills, time estimation, and cognitive deficit ( 43 , 44 ). The dyslexic individuals in Chinese languages showed several impairments in the sensorimotor domain such as balance, motor skills, rapid processing, morphological awareness, and orthographic deficits ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Hyperviscosity manifests as cerebral infarction caused by monoclonal immunoglobulinm (IgM) protein in the blood. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%